A comparative evaluation of gabapentin and clonidine for attenuating pressor responses to laryngoscopy and endotracheal intubation in hypertensive patients-A prospective double-blinded clinical study - Richa Parihar; Anju Gautam; Nancy Ekka; Shikha Goyal (Asian Journal of Medical Sciences, 2023)
Background: Endotracheal intubation forms an indispensable part of general anesthesia. Various adjuvants have been added to diminish the hemodynamic stress response associated with it. These changes are more marked in hypertensive individuals. Aims and Objectives: The aim of the present study was to compare the efficacy of oral clonidine and oral gabapentin and their associated side effects if any; for attenuation of hemodynamic responses following laryngoscopy and tracheal intubation in hypertensive patients. Materials and Methods: A total of 108 hypertensive patients with American Society of Anesthesiologists grade II/III scheduled for elective surgeries requiring general anesthesia were randomly allocated into three groups receiving Group G Tablet gabapentin 800 mg, Group C Tablet clonidine 0.2 mg, and Group P placebo (multivitamin tablets) given 2 h before surgery with a sip of water. The hemodynamic parameters such as heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and adverse events during the perioperative period were noted. The statistical analysis was done by paired t-test, ANOVA, and Chi-square test and by SPSS22 software. Results: The demographic data were comparable in all three groups. There was no significant difference at baseline for HR, SBP, DBP, and MBP in all three groups. The mean HR was significantly lower in Group C as compared to Group G and Group P (P<0.013). The mean SBP, DBP, and MBP was significantly lower in Groups C and G as compared to Group P (P<0.01) before induction, after induction after laryngoscopy and intubation, then at 5, 10, 15, 20, 25, and 30 min after intubation. Conclusion: Clonidine and gabapentin in the abovementioned doses can be safely used for attenuating hemodynamic stress response. Clonidine proved to have better hemodynamic stability and tends to be more effective in attenuating pressor response laryngoscopy and intubation in hypertensive patients when compared to gabapentin.